2003
DOI: 10.1063/1.1625788
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, optical, and magnetic properties of diluted magnetic semiconductor Zn1−xMnxO nanowires via vapor phase growth

Abstract: Diluted magnetic semiconductor Zn1−xMnxO nanowires were synthesized via an in situ doping of manganese in ZnO nanowires using vapor phase growth at 500 °C. The maximum content of the manganese in the ZnO is around 13 at. %, approaching the maximum thermal equilibrium limit of Mn solubility in ZnO at the growth temperature. Structure and composition analysis revealed that the manganese was doped into the lattice structure, forming solid solution instead of precipitation. Magnetic property measurements revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(98 citation statements)
references
References 19 publications
1
92
0
3
Order By: Relevance
“…Controlled doping of ZnO nanowires has indeed led to diverse applications in recent years such as photodetectors [8], p-n homojunction rectifiers [9], sensors [10], light-emitting diodes [11], piezoelectric generators [12], field-effect transistors [13], and field emitters [14]. Likewise, doping ZnO nanowires with transition metals [15][16][17] or rare-earth elements [18,19] makes them candidate building blocks in bottom-up assembly of spintronic devices. To add to the foregoing cases, we will show that the functional properties of ZnO nanowires could further be diversified by doping with Bi, making them candidate materials for spinorbitronic [20] applications.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled doping of ZnO nanowires has indeed led to diverse applications in recent years such as photodetectors [8], p-n homojunction rectifiers [9], sensors [10], light-emitting diodes [11], piezoelectric generators [12], field-effect transistors [13], and field emitters [14]. Likewise, doping ZnO nanowires with transition metals [15][16][17] or rare-earth elements [18,19] makes them candidate building blocks in bottom-up assembly of spintronic devices. To add to the foregoing cases, we will show that the functional properties of ZnO nanowires could further be diversified by doping with Bi, making them candidate materials for spinorbitronic [20] applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, un- [20,22]. Mn 3 O 4 is ferromagnetic ordering, and its Curie temperature is around 44 K [23]. It is already reported that the curie temperature of ZnMnO and ZnMn 2 O 3 like phase are well above 300 K [20,24,25].…”
Section: M-h Curvementioning
confidence: 96%
“…The above results are supported by modeling results (Wang and Qian, 2006) although carrier mediated exchange has not yet to be experimentally verified in nanowires. Similarly, high Curie temperatures have been observed in other transition metal doped semiconductor nanostructures such as II-VI (including ZnO (Chang et al, 2003, Cui and Gibson, 2005, Baik and Lee, 2005, ZnS (Brieler et al, 2004, Radovanovic et al, 2005, CdS (Radovanovic et al, 2005)) and III-V (including GaN (Radovanovic et al, 2005, Choi et al, 2005b, GaAs (Jeon et al, 2004)), but only inconclusive reports have been published on the magneto-electric transport in these nanostructures. It could be attributed to the complicated ferromagnetic properties caused by precipitates, second-phase alloys and nanometer-scale clusters.…”
Section: Introductionmentioning
confidence: 99%